Extended Neonatal Jaundice Associated with Congenital Myxedema - Claudia Olaru; Maria Florea; Anamaria Burlea; Gabriela Paduraru; Valeriu V. Lupu; Smaranda Diaconescu (Romanian Society of Oral Rehabilitation, 2012)
Congenital hypothyroidism/ myxedema is inadequate thyroid hormone production in newborn infants. This can occur because of an anatomic defect in the gland, an inborn error of thyroid metabolism, iodine deficiency. There is an inverse relationship between age at diagnosis and intelligence quotient (IQ) later in life. Most newborn babies with congenital hypothyroidism have few or no clinical manifestations of thyroid deficiency, and the majority of cases are sporadic. Female infant, aged 21 days, is hospitalized in our clinic for investigations, presenting prolonged jaundice. Clinical examination on admission revealed skin and mucous jaundice, throat congestion, nasal obstruction, discrete macroglossia with tongue protrusion. Laboratory investigations revealed predominant indirect hyperbilirubinemia, increased hepatic cytolysis tests. Toxoplasma infectious mononucleosis and cytomegalovirus antibodies were normal. Investigation of thyroid function revealed low FT4 and TSH increased. Endocrinological examination established diagnosis of hypothiroidism